Preparation method of ultrahigh-hardness polyurethane elastomer polishing material

High-content prepolymers are synthesized through special structural polyols, and ultra-high hardness polyurethane elastomers are prepared using one-step method and double vacuum process, which solves the problem of insufficient hardness of traditional polyurethane elastomers and achieves high-efficiency polishing and good wear resistance and oxidation resistance.

CN119708420APending Publication Date: 2025-03-28ZHONGJI SEMICON MATERIALS (SHENZHEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411892737.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional polyurethane elastomers have shortcomings in hardness and cannot meet the polishing needs of high-end materials such as superhard alloys, optical glass and semiconductor chips, resulting in low polishing efficiency and degradation of optical performance.

Method used

High-content prepolymers are synthesized by special structural polyols, and ultra-high hardness polyurethane elastomers are prepared using one-step method and double vacuum process. The method includes synthesis of high content prepolymers under the protection of inert gas, and then further preparing ultra-high hardness polyurethane elastomers by a one-step process and a double vacuum process.

Benefits of technology

It significantly improves the hardness of polyurethane elastomer, improves polishing efficiency and effect, ensures a high-quality polishing surface, and has good wear resistance and oxidation resistance, extending the service life of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention is applied to the technical field of high polymer materials, and discloses a preparation method of an ultrahigh-hardness polyurethane elastomer polishing material, and the preparation method comprises the following steps: S1, synthesizing a high-content prepolymer through a polyhydric alcohol with a special structure; and S2, preparing the ultrahigh-hardness polyurethane elastomer on the basis of the high-content prepolymer obtained in the step S1 by utilizing a one-step method and combining a dual-vacuumizing process. According to the preparation method of the ultrahigh-hardness polyurethane elastomer polishing material, the high-content prepolymer is synthesized by adopting the polyhydric alcohol with a specific structure, and the hardness of the ultrahigh-hardness polyurethane elastomer prepared on the basis is greatly improved, so that when the ultrahigh-hardness polyurethane elastomer polishing material is used for polishing hard materials such as superhard alloy and optical glass, the polishing efficiency and effect are remarkably improved, and the service life of the ultrahigh-hardness polyurethane elastomer polishing material is prolonged. Meanwhile, the inherent elasticity of the polyurethane elastomer is reserved, effective buffering can be achieved in the process of making contact with a workpiece, the surface of the workpiece is prevented from being scratched, and high quality and integrity of the polished surface are guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a method for preparing an ultra-high hardness polyurethane elastomer polishing material. Background Art

[0002] In the cutting-edge field of material processing and manufacturing today, polishing technology is a key link in improving the surface quality and precision of materials. Its importance is self-evident. Traditional polishing materials, such as aluminum oxide and silicon carbide, have occupied a certain position in many polishing applications due to their own characteristics. Aluminum oxide has high hardness and chemical stability, and silicon carbide has excellent hardness and grinding performance. It has been widely used in the polishing of metals, ceramics and other materials for a long time. However, with the rapid development of science and technology, especially in the processing and manufacturing of high-end materials such as super-hard alloys, optical glass, and semiconductor chips, traditional polishing materials have gradually revealed their limitations. Super-hard alloys are widely used in aerospace, high-end molds and other fields due to their excellent strength and wear resistance, but traditional polishing materials are difficult to achieve efficient and high-precision surface treatment when polishing them. Optical glass has extremely high requirements for surface flatness and finish. Ordinary polishing materials are difficult to meet its nano-level polishing precision requirements, which easily leads to a decrease in optical performance. The manufacture of semiconductor chips requires damage-free and high-precision polishing at a microscopic scale, and the performance of traditional materials in this regard is unsatisfactory;

[0003] As a type of high-performance polymer material, polyurethane elastomers have shown their potential in the polishing field with their good elasticity, outstanding wear resistance and a certain degree of chemical corrosion resistance. They are regarded as a new type of polishing material with potential. However, conventional polyurethane elastomers have obvious deficiencies in hardness, and their hardness level cannot match the stringent requirements for precision polishing of the above-mentioned high-end materials. When polishing super-hard alloys, low-hardness polyurethane elastomers cannot provide sufficient cutting force, resulting in low polishing efficiency, a lot of time and cost. For the polishing of optical glass, insufficient hardness will cause tiny defects to remain on the polished surface, affecting the transmission and refraction of light, and thus reducing the performance of optical components. In semiconductor chip manufacturing, low-hardness polishing materials may cause scratches on the chip surface and damage to the microstructure, seriously affecting the quality and reliability of the chip. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing an ultra-high hardness polyurethane elastomer polishing material to solve the problem of insufficient hardness of common polyurethane elastomers mentioned in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing an ultra-high hardness polyurethane elastomer polishing material, the preparation method comprising the following steps:

[0006] S1: Synthesize high content prepolymers through special structure polyols;

[0007] S2: Using a one-step method combined with a double vacuum process, an ultra-high hardness polyurethane elastomer is prepared based on the high content prepolymer obtained in S1;

[0008] The special structure polyol in S1 is a polyol containing a polyether or polyester structure, and the functionality of the polyol is 2-4, and the molecular weight ranges from 500-2000;

[0009] The polyol in S1 has a polyether structure formed by polymerization of propylene oxide, ethylene oxide or a copolymer thereof as a monomer, and a polyester structure formed by condensation of a dibasic acid and a diol, wherein the dibasic acid is one of adipic acid or phthalic acid, and the diol is one of ethylene glycol or propylene glycol;

[0010] The reaction of synthesizing the high-content prepolymer in S1 is carried out under the protection of an inert gas and a chain extender is added, wherein the inert gas is one of nitrogen or argon, and the gas flow rate of the inert gas is 10-30 mL / min;

[0011] The reaction temperature for synthesizing the high-content prepolymer is 60-90° C., the catalyst is an organic tin catalyst, and the amount of the catalyst is 0.05%-0.2% of the total mass of the polyol and the isocyanate, the reaction time is 2-4 hours, and mechanical stirring is used during the reaction, the stirring paddle is one of anchor type or paddle type, and the stirring speed is 150-300 rpm;

[0012] The organotin catalyst is one of dibutyltin dilaurate or stannous octoate;

[0013] The one-step process in S2 comprises the following steps:

[0014] The mixing order of the raw materials is to first add the polyol into the reaction container, stir at a stirring speed of 300-500 rpm for 5-10 minutes, then add the isocyanate and antioxidant, the mixing speed is 400-600 rpm, the mixing time is 1-3 minutes, and the reaction starting temperature is 60-80°C;

[0015] In the double vacuum process steps:

[0016] The first vacuuming pressure is 5-10 kPa and lasts for 10-20 minutes to remove low-boiling impurities and moisture in the reaction system;

[0017] The second vacuuming is performed to a pressure of 1-3 kPa for 30-60 minutes to promote the polymerization reaction and reduce internal bubble defects;

[0018] The time interval between two vacuuming is 5-10 minutes. During the vacuuming process, the reaction vessel adopts a jacket structure, and circulating cooling water is passed through the jacket, and the water temperature is controlled at 10-20°C.

[0019] Preferably, the chain extender in S1 is one or more of 1,4-butanediol, ethylene glycol or hexamethylenediamine, and the added amount of the chain extender is 2%-8% of the mass of the polyol.

[0020] By adopting the above technical solution, the molecular weight and segment structure of the polyurethane elastomer can be effectively adjusted, and the hardness, elasticity and other properties of the material can be accurately controlled, so that it can better meet the specific requirements of material performance in different polishing scenarios, while ensuring that the material has good reactivity and molding effect during the preparation process.

[0021] Preferably, the antioxidant in S2 is one of a hindered phenol antioxidant or a phosphite antioxidant, and the added amount of the antioxidant is 0.1%-0.5% of the mass of the polyurethane elastomer.

[0022] The adoption of the above technical solution can effectively improve the anti-oxidation performance of the material, extend its service life and meet the needs of long-term use.

[0023] Preferably, the isocyanate in S2 is one or more of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI) or isophorone diisocyanate (IPDI), and the molar ratio of isocyanate to polyol is 1.2-1.5:1.

[0024] By adopting the above technical solution, the type of isocyanate can be flexibly selected according to different usage scenarios and performance requirements, and the hardness, elasticity and other performance indicators of the material can be accurately controlled.

[0025] Preferably, an ultrasonic oscillator is provided in the S2 reaction container, and the ultrasonic frequency is 20-50kHz and the power is 100-500W.

[0026] By adopting the above technical solution, the cavitation effect of ultrasound can promote more uniform mixing of raw materials, accelerate the reaction process, and improve the uniformity and quality stability of materials.

[0027] Preferably, the inner wall of the S2 reaction container is coated with a polytetrafluoroethylene coating to prevent the reaction raw materials from adhering to the container wall, ensure that the reaction is fully carried out and facilitate post-reaction cleaning, and the thickness of the polytetrafluoroethylene coating is 0.1-0.5 mm.

[0028] The adoption of the above technical solution reduces the waste of raw materials, reduces the difficulty of cleaning, and improves the production efficiency and the reuse rate of equipment.

[0029] Preferably, the ultra-high hardness polyurethane elastomer in S2 is post-treated after preparation to eliminate internal stress and stabilize material properties, and the post-treatment process is heat treatment at 80-100° C. for 2-6 hours and then placed at room temperature for 24-72 hours.

[0030] The use of the above technical solution can effectively eliminate the stress caused by the polymerization reaction inside the material, making the physical properties of the material more stable and reliable and reducing the risk of deformation and cracking during use.

[0031] Preferably, after adding isocyanate to S2, the reaction is carried out in a gradient heating manner, with a heating rate of 5-10°C / min, from room temperature to 80-100°C and maintained for 30-60 minutes.

[0032] The above technical solution makes the reaction process smooth and orderly, which is conducive to the full reaction of each component, forming a more regular and stable polymer structure and improving the comprehensive performance of the material.

[0033] Preferably, during the second vacuuming in S2, a small amount of inert gas pulses are intermittently introduced into the reaction container, the pulse time interval is 2-5 minutes, and the gas volume of each pulse is 0.1%-0.5% of the volume of the reaction container.

[0034] The above technical solution is adopted to further promote the escape of bubbles and the uniform mixing of the reaction system, while avoiding the reaction process being affected by excessive vacuum causing the reaction system pressure to be too low.

[0035] Compared with the prior art, the invention has the following beneficial effects: the preparation method of the ultra-high hardness polyurethane elastomer polishing material:

[0036] 1. The hardness of the ultra-high hardness polyurethane elastomer prepared by synthesizing high-content prepolymers with specific structure polyols is greatly improved, which can provide sufficient cutting force when polishing hard materials such as super-hard alloys and optical glass, and significantly enhance the polishing efficiency and effect. At the same time, the material also retains the inherent elasticity of the polyurethane elastomer, which can effectively buffer the contact with the workpiece to avoid scratches on the workpiece surface, ensure the high quality and integrity of the polished surface, and has good wear resistance. It can maintain stable performance during long-term polishing operations, extend the service life of the material, and reduce polishing costs;

[0037] 2. The one-step method combined with the double vacuum process can effectively reduce side reactions and improve product purity and quality stability through precise setting of process parameters. The steps are clear and the operability is strong, which is convenient for industrial large-scale production.

[0038] 3. An ultrasonic oscillator is installed in the reaction vessel to generate an oscillation effect during the mixing and reaction of the raw materials, which promotes full contact and reaction of the components, significantly improves the uniformity and performance stability of the materials, and makes the quality of the final product more reliable. The polytetrafluoroethylene coating on the inner wall of the container effectively prevents the reaction raw materials from adhering to the wall surface, ensures the full reaction, avoids incomplete reaction and quality fluctuations caused by residual raw materials, and greatly facilitates the cleaning work after the reaction, reduces equipment maintenance time and cost, improves the utilization efficiency of production equipment, and shortens the production cycle. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The invention provides a technical solution: a method for preparing an ultra-high hardness polyurethane elastomer polishing material.

[0041] Embodiment 1:

[0042] Ratio:

[0043] Polyol: Select polyether polyol (polymerized with propylene oxide as monomer) with a molecular weight of 1000 and a functionality of 3, with a mass of 100g;

[0044] Chain extender: 1,4-butanediol, the addition amount is 5% of the mass of the polyol, i.e. 5g;

[0045] Isocyanate: diphenylmethane diisocyanate (MDI), the molar ratio of isocyanate to polyol is 1.3:1;

[0046] Antioxidant: Hindered phenol antioxidant, added in an amount of 0.3% of the mass of the polyurethane elastomer;

[0047] Example steps:

[0048] S1: under nitrogen protection (gas flow rate of 20 mL / min), add polyol into the reaction vessel, add dibutyltin dilaurate catalyst (the amount is 0.1% of the total mass of polyol and isocyanate) at 75°C, add chain extender 1,4-butanediol, use a paddle stirring paddle, the stirring speed is 200 rpm, and react for 3 hours to synthesize a high-content prepolymer;

[0049] S2: First, add the polyol into the reaction vessel, stir at a stirring speed of 400 rpm for 8 minutes, then add the isocyanate and antioxidant, the mixing speed is 500 rpm, the mixing time is 2 minutes, the reaction starting temperature is 70°C, the first vacuum pressure is 8 kPa, the duration is 15 minutes, the second vacuum pressure is 2 kPa, the duration is 45 minutes, the time interval between the two vacuums is 8 minutes, during the vacuum process, the jacket of the reaction vessel is circulated with cooling water, the water temperature is controlled at 15°C, and an ultrasonic vibrator is set in the reaction vessel. The ultrasonic frequency is 30kHz and the power is 300W. The inner wall of the reaction container is coated with a 0.3mm thick polytetrafluoroethylene coating. After adding isocyanate, the reaction is carried out by gradient heating. The heating rate is 8℃ / min, from room temperature to 90℃ and maintained for 45 minutes. During the second vacuuming, a small amount of nitrogen pulses are intermittently introduced into the reaction container. The pulse time interval is 3 minutes, and the gas volume of each pulse is 0.3% of the volume of the reaction container. After the preparation is completed, it is heat treated at 90℃ for 4h and then placed at room temperature for 48h.

[0050] Experimental results:

[0051] Hardness test: measured with a Shore D hardness tester, the hardness value is 85;

[0052] Surface roughness: The surface of the polished sample was tested using a roughness meter, and the roughness Ra reached 0.05μm;

[0053] Bubble rate: Observing the cross section through a microscope, the volume of internal bubbles accounts for about 0.5%;

[0054] Polishing efficiency: Polishing tests on stainless steel samples showed that under the same time and pressure conditions, the material removal rate was increased by 30% compared with traditional polyurethane polishing materials;

[0055] Material loss rate: After 10 polishing cycles, the material mass loss is about 5%.

[0056] Embodiment 2:

[0057] Ratio:

[0058] Polyol: Select polyester polyol (formed by condensation of adipic acid and ethylene glycol) with a molecular weight of 1500 and a functionality of 2, with a mass of 80g;

[0059] Chain extender: ethylene glycol, added in an amount of 3% of the mass of the polyol, i.e. 2.4 g;

[0060] Isocyanate: toluene diisocyanate (TDI), the molar ratio of isocyanate to polyol is 1.4:1;

[0061] Antioxidant: phosphite antioxidant, the addition amount is 0.2% of the mass of polyurethane elastomer;

[0062] Example steps:

[0063] S1: under argon protection (gas flow rate of 15 mL / min), add polyol into the reaction vessel, add stannous octoate catalyst (the amount is 0.15% of the total mass of polyol and isocyanate) at 80°C, add chain extender ethylene glycol, use anchor stirring paddle, stirring speed is 250 rpm, react for 2.5 hours to synthesize high content prepolymer;

[0064] S2: First add the polyol into the reaction vessel, stir at a stirring speed of 350 rpm for 6 minutes, then add the isocyanate and antioxidant, the mixing speed is 450 rpm, the mixing time is 1.5 minutes, the reaction starting temperature is 75°C, the first vacuum pressure is 6 kPa, the duration is 12 minutes, the second vacuum pressure is 1.5 kPa, the duration is 50 minutes, the time interval between the two vacuums is 6 minutes, during the vacuum process, the jacket of the reaction vessel is circulated with cooling water, the water temperature is controlled at 12°C, and an ultrasonic Oscillator, ultrasonic frequency of 25kHz, power of 200W, the inner wall of the reaction container is coated with a 0.2mm thick polytetrafluoroethylene coating, after adding isocyanate, the reaction is carried out by gradient heating, the heating rate is 6℃ / min, from room temperature to 95℃ and maintained for 50 minutes, during the second vacuuming, a small amount of argon pulses are intermittently introduced into the reaction container, the pulse time interval is 2.5 minutes, and the gas volume of each pulse is 0.2% of the volume of the reaction container, after the preparation is completed, it is heat treated at 95℃ for 3h, and then placed at room temperature for 36h;

[0065] Experimental results:

[0066] Hardness test: Shore D hardness is 78;

[0067] Flexibility: In the bending test, no cracks were generated after bending 100 times on a cylinder with a radius of 5 mm;

[0068] Wear resistance: Using Taber wear tester, the wear loss is 25mg / 1000 revolutions;

[0069] Polishing effect: After polishing the aluminum alloy workpiece, the surface finish is significantly improved, and the number of scratches is reduced by 90% compared with before polishing;

[0070] Service life: In continuous polishing operation, it can maintain effective polishing performance for up to 15 hours.

[0071] Embodiment three:

[0072] Ratio:

[0073] Polyol: Select polyether polyol with a molecular weight of 800 and a functionality of 4 (polymerized with ethylene oxide as a monomer), with a mass of 120g;

[0074] Chain extender: hexamethylenediamine, the addition amount is 6% of the mass of the polyol, i.e. 7.2g;

[0075] Isocyanate: isophorone diisocyanate (IPDI), the molar ratio of isocyanate to polyol is 1.25:1;

[0076] Antioxidant: Hindered phenol antioxidant, added in an amount of 0.4% of the mass of the polyurethane elastomer;

[0077] Example steps:

[0078] S1: under nitrogen protection (gas flow rate of 25 mL / min), add polyol into the reaction vessel, add dibutyltin dilaurate catalyst (the amount is 0.08% of the total mass of polyol and isocyanate) at 65°C, add hexamethylenediamine as a chain extender, use a paddle stirring paddle, the stirring speed is 180 rpm, and react for 3.5 hours to synthesize a high-content prepolymer;

[0079] S2: First, add the polyol into the reaction vessel, stir at a stirring speed of 450 rpm for 7 minutes, then add the isocyanate and antioxidant, the mixing speed is 550 rpm, the mixing time is 2.5 minutes, the reaction starting temperature is 65°C, the first vacuum pressure is 9 kPa, the duration is 18 minutes, the second vacuum pressure is 2.5 kPa, the duration is 55 minutes, the time interval between the two vacuums is 9 minutes, during the vacuum process, the jacket of the reaction vessel is circulated with cooling water, the water temperature is controlled at 18°C, and an ultrasonic The ultrasonic oscillator has an ultrasonic frequency of 40kHz and a power of 400W. The inner wall of the reaction container is coated with a 0.4mm thick polytetrafluoroethylene coating. After adding isocyanate, the reaction is carried out by gradient heating. The heating rate is 9℃ / min, from room temperature to 85℃ and maintained for 55 minutes. During the second vacuuming, a small amount of nitrogen pulses are intermittently introduced into the reaction container. The pulse time interval is 4 minutes, and the gas volume of each pulse is 0.4% of the volume of the reaction container. After the preparation is completed, it is heat treated at 85℃ for 5h and then placed at room temperature for 60h.

[0080] Experimental results:

[0081] Hardness test: Shore D hardness reaches 90;

[0082] Elastic recovery rate: After compression deformation of 50%, the elastic recovery rate is 95%;

[0083] Polishing uniformity: After polishing the ceramic sample, the surface hardness deviation is within ±5%;

[0084] Finish: Surface roughness Ra can reach 0.03μm;

[0085] Stability: After being placed in an environment with a humidity of 50%-80% and a temperature of 20℃-30℃ for 30 days, the hardness change rate is within ±2%.

[0086] How to use ultra-high hardness polyurethane elastomer polishing material:

[0087] 1. Preparation stage:

[0088] According to the shape, size and polishing process requirements of the material to be polished (such as metal, ceramic or optical glass), select ultra-high hardness polyurethane elastomer polishing materials with suitable shapes (block, column, disc or sphere, etc.) to ensure that its molding accuracy meets the requirements (±0.1-±0.5 mm);

[0089] For polishing metal materials, prepare aqueous coolant and connect the coolant supply system to the polishing equipment, setting the coolant flow rate to 10-30 ml / min;

[0090] For polishing ceramic or optical glass materials, prepare perfluoropolyether coolant and set its flow rate to 5-15 ml / min.

[0091] 2. Installation and debugging:

[0092] Install the ultra-high hardness polyurethane elastomer polishing material on the polishing head or workbench of the polishing equipment, ensuring that it is firmly installed and has good concentricity to avoid shaking or deviation during the polishing process;

[0093] Debug the polishing equipment, set the polishing pressure to 0.1-0.5MPa, the polishing speed to 500-1500rpm, and add abrasives with a particle size of 1-100 microns on the surface of the polishing material as needed. The amount of abrasive added is 5%-20% of the mass of the polyurethane elastomer;

[0094] 3. Polishing operation:

[0095] Start the polishing equipment and coolant supply system, make the polishing material contact with the surface of the material to be polished and start the polishing operation. During the polishing process, keep the polishing parameters stable and closely observe the polishing surface quality and material wear;

[0096] For long-term or batch polishing operations, the wear degree of the polishing material can be checked regularly. When it is found that the polishing effect has declined, the polishing parameters can be adjusted according to the situation to maintain better polishing efficiency and quality.

[0097] 4. Maintenance and regeneration:

[0098] After the polishing operation is completed, turn off the polishing equipment and coolant supply system, and clean the polishing equipment and work area;

[0099] If the performance of the ultra-high hardness polyurethane elastomer polishing material decreases after being used for a period of time, a regeneration process can be used to restore some of its polishing performance. The used elastomer is soaked in an organic solvent for 2-6 hours, and then dried in a vacuum drying oven at 60-80°C for 12-24 hours to remove surface impurities and adsorbents. It is then heat treated at a temperature of 100-120°C for 1-3 hours to restore some of the performance of the material's internal structure. The regenerated polishing material can be put into use again.

[0100] The above specific embodiments further illustrate the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific embodiments of the present invention and do not limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the protection scope of the present invention.

Claims

1. A method for preparing an ultra-high hardness polyurethane elastomer polishing material, characterized in that: The preparation method comprises the following steps: S1: Synthesize high content prepolymers through special structure polyols; S2: Using a one-step method combined with a double vacuum process, an ultra-high hardness polyurethane elastomer is prepared based on the high content prepolymer obtained in S1; The special structure polyol in S1 is a polyol containing a polyether or polyester structure, and the functionality of the polyol is 2-4, and the molecular weight ranges from 500-2000; The polyol in S1 has a polyether structure formed by polymerization of propylene oxide, ethylene oxide or a copolymer thereof as a monomer, and a polyester structure formed by condensation of a dibasic acid and a diol, wherein the dibasic acid is one of adipic acid or phthalic acid, and the diol is one of ethylene glycol or propylene glycol; The reaction of synthesizing the high-content prepolymer in S1 is carried out under the protection of an inert gas and a chain extender is added, wherein the inert gas is one of nitrogen or argon, and the gas flow rate of the inert gas is 10-30 mL / min; The reaction temperature for synthesizing the high-content prepolymer is 60-90° C., the catalyst is an organic tin catalyst, and the amount of the catalyst is 0.05%-0.2% of the total mass of the polyol and the isocyanate, the reaction time is 2-4 hours, and mechanical stirring is used during the reaction, the stirring paddle is one of anchor type or paddle type, and the stirring speed is 150-300 rpm; The organotin catalyst is one of dibutyltin dilaurate or stannous octoate; The one-step process in S2 comprises the following steps: The mixing order of the raw materials is to first add the polyol into the reaction container, stir at a stirring speed of 300-500 rpm for 5-10 minutes, then add the isocyanate and antioxidant, the mixing speed is 400-600 rpm, the mixing time is 1-3 minutes, and the reaction starting temperature is 60-80°C; In the double vacuum process steps: The first vacuuming pressure is 5-10 kPa and lasts for 10-20 minutes to remove low-boiling impurities and moisture in the reaction system; The second vacuuming is performed to a pressure of 1-3 kPa for 30-60 minutes to promote the polymerization reaction and reduce internal bubble defects; The time interval between two vacuuming is 5-10 minutes. During the vacuuming process, the reaction vessel adopts a jacket structure, and circulating cooling water is passed through the jacket, and the water temperature is controlled at 10-20°C.

2. The method for preparing a super-high hardness polyurethane elastomer polishing material according to claim 1, characterized in that: The chain extender in S1 is one or more of 1,4-butanediol, ethylene glycol or hexamethylenediamine, and the added amount of the chain extender is 2%-8% of the mass of the polyol.

3. The method for preparing a super-high hardness polyurethane elastomer polishing material according to claim 1, characterized in that: The antioxidant in S2 is one of hindered phenol antioxidants or phosphite antioxidants, and the added amount of the antioxidant is 0.1%-0.5% of the mass of the polyurethane elastomer.

4. The method for preparing a super-high hardness polyurethane elastomer polishing material according to claim 1, characterized in that: The isocyanate in S2 is one or more of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI) or isophorone diisocyanate (IPDI), and the molar ratio of isocyanate to polyol is 1.2-1.5:

1.

5. The method for preparing a super-high hardness polyurethane elastomer polishing material according to claim 1, characterized in that: An ultrasonic oscillator is arranged in the S2 reaction container, and the ultrasonic frequency is 20-50kHz and the power is 100-500W.

6. The method for preparing a super-high hardness polyurethane elastomer polishing material according to claim 1, characterized in that: The inner wall of the S2 reaction container is coated with a polytetrafluoroethylene coating to prevent the reaction raw materials from adhering to the container wall, ensure the reaction is fully carried out and facilitate post-reaction cleaning, and the thickness of the polytetrafluoroethylene coating is 0.1-0.5mm.

7. The method for preparing a super-high hardness polyurethane elastomer polishing material according to claim 1, characterized in that: After the preparation of the ultra-high hardness polyurethane elastomer in S2 is completed, it is post-treated to eliminate internal stress and stabilize material properties. The post-treatment process is heat treatment at 80-100° C. for 2-6 hours and then placed at room temperature for 24-72 hours.

8. The method for preparing a super-high hardness polyurethane elastomer polishing material according to claim 1, characterized in that: After adding isocyanate to S2, a gradient temperature rise method is used to react, with a heating rate of 5-10°C / min, from room temperature to 80-100°C and maintained for 30-60 minutes.

9. The method for preparing a super-high hardness polyurethane elastomer polishing material according to claim 1, characterized in that: During the second vacuuming of S2, a small amount of inert gas pulses are intermittently introduced into the reaction container, the pulse time interval is 2-5 minutes, and the gas volume of each pulse is 0.1%-0.5% of the volume of the reaction container.